Functionalized platinum nanoparticles with surface charge trigged by pH: synthesis, characterization and stability studies - Testa, Giovanna; Fontana, Laura; Venditti, Iole; Fratoddi, Ilaria (Beilstein Journal of Nanotechnology, 2016)
In this work, the synthesis and characterization of functionalized platinum nanoparticles (PtNPs) have been investigated. PtNPs were obtained by a wet redox procedure using 2-diethylaminoethanethiol hydrochloride (DEA) as capping agent. By varying the Pt/thiol molar ratio, monodispersed and stable particles with diameters in the range of 3–40 nm were isolated. The amino functionality allows neutral particles to be obtained in basic water solution and positive charged nanoparticles in neutral or acidic water solution (pH 7–2), as confirmed by DLS and ζ-potential measurements. FTIR spectroscopy, FE-SEM, DLS and ζ-potential measurements confirmed the size and showed long term water stability (up to three months) of the colloidal system.
Keywords: functionalized platinum nanoparticles; pH responsive materials; synthesis of metal nanoparticles; thiol functionalization